Debris from the original temple assembled in parts to form the jagati - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple. The base has an ardha padma (half lotus) surrounded by geometric patterns. The panel in the middle has an ornate bird, probably a mayura (peacock), bordered by a creeping vine motif. The next two levels are mouldings depicting floral and vine patterns.